Praxeological analysis of grade V elementary school mathematics textbooks on fractions - Devi Rahayu; Didi Suryadi (AXIOM : Jurnal Pendidikan dan Matematika, 2026)
Textbooks are essential instruments in implementing the Merdeka Curriculum, serving as a bridge between curriculum policy and classroom practices. However, didactic challenges often arise when the presentation of material becomes confined to mechanical procedures rather than fostering deep conceptual understanding, particularly in fractions, which are highly abstract for elementary students. This study aims to analyze Grade V mathematics textbooks under the Merdeka Curriculum, focusing on fractions, through a praxeological lens. The analysis applies the four components of praxeology, task type (T), technique (τ), technology (θ), and theory (Θ), to evaluate the extent to which textbooks support effective learning. Using qualitative document analysis, data were drawn from the 2022 Grade V Mathematics Textbook published by the Ministry of Education, Culture, Research, and Technology, with attention to the relationship between the praxis block (tasks and techniques) and the logos block (technology and theory). Findings reveal that although the textbook integrates visual approaches and real-world contexts (such as local culture), procedural aspects remain dominant. A praxeological paradox was identified by visual illustrations often serve merely as technical justification (technology) without sufficient conceptual exploration (theory). Moreover, the limited variety of representations and rigid techniques in mixed operations risk reinforcing natural number bias and creating learning obstacles. The structure of fraction material in the textbook tends to prioritize procedural-mechanical aspects over independent conceptual exploration. More flexible and holistic instructional designs in textbooks are needed to reduce individual-instructional learning and to foster students' ability to generalize concepts to a broader mathematical domain.